Stereotypic Formulas of Business Documents and Monuments of Common Language of Moscow Rus’ in 16th and 17th Centuries (Systematizing Approach) - E. I. Zinovyeva (Научный диалог, 2023)
The relevance of the article is determined by the insufficient study of stable verbal complexes in the language of the XVI—XVII centuries — the initial stage of the formation of the Russian national language. The novelty of the study can be seen in the systematization of a separate category of data stable units — formulas that function in texts of this period that differ in genre. The term stereotypic formulas is introduced, and its definition is offered. The purpose of the article is a comprehensive description of the material for further presentation in the historical differentiated phraseological dictionary. The classification of the analyzed stereotypical formulas is given according to various criteria: the degree of prevalence in business and everyday language texts of the period under study, in accordance with the form of the document, from the point of view of structure. Particular attention is paid to the linguistic and sociocultural aspect of the analyzed units consideration: the identification of their linguistic and cultural potential, historical and social conditioning in the considered period, the ability to act as a symbol, the need for decoding for modern speakers of the language. It is concluded that stereotyped formulas represent a systematic dictionary association of units of different degrees of stability and different structure. Problems that require solutions in the lexicographic description of stereotyped formulas are defined.